Konsep Toleransi Dalam Susut Pandang Ormas Aswaja Dan Implikasinya Terhadap Pembelajaran Pendidikan Agama Islam - Abu Warasy Batula; Ayu Wulandari; Bilqis Nafilah Febrianti; Silvia Siti Rachmawaty; Muhamad Parhan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The concept of tolerance is an important thing to study, especially in a pluralistic society with different ethnicities, nations, races and religions. This study discusses the concept of tolerance from the viewpoint of Ahlussunnah wal Jamaah, in order to examine the concept of tolerance in literature from the Nahdhatul Ulama, Muhammadiyah, and Islamic Unity fronts (FPI) so that it can be implemented in life, especially in Islamic education learning. The research method used is a qualitative method with a literature study approach. The results of the study show that from the perspective of Ahlussunnah wal Jamaah tolerance is an important principle in building brotherhood and harmony among religious communities by emphasizing the importance of equality in rights and obligations without discrimination. In line with that, the application of the concept of tolerance in PAI learning can be through religious education curriculum content which is not only dominated by worship and belief material, but material about the harmonious life of fellow human beings which is implemented through religious tolerance. Instilling the concept of tolerance in PAI learning can also be implemented with an emphasis on PAI teachers in tolerance learning practices and assisted by significant learning materials that assist in tolerance learning both in early childhood education, elementary schools, junior high schools, high schools even in study bench.